Cleaning of sewageswith use of pinotenk - Semenova, Olena; Bublienko, Natalia; Shylofost, Tatiana; Semenova, Alexandra; Reshetnyak, Lyudmila (My University, 2016)
Characterized sewage containing hydrocarbons. It is shown that their purification is a complex biological process. This is due to the peculiarities of dissolving contaminated components in water. The use of the biosorption process for wastewater treatment with such contaminations is proposed. The principle of work of a pinotek, its advantages, features of use is given. The indicators of wastewater pollution before and after cleaning are shown.
Keywords: sewage; biological purification; active sludge; biosorption; pinotehnok; стічні води; біологічне очищення; активний мул; біосорбція; пінотенк; сточные воды; биологическая очистка; активный ил; биосорбции; пинотенк; кафедра біотехнології і мікробіології